Promoting students success with a business intelligence system - Piedade, Maria Beatriz (2010)
The promotion of the students’ success is usually associated to the closely monitoring of the students’ activities. This requires the implementation of mechanisms that, in the scope of the teaching/learning process, allow the students’ academic activities monitoring, the students’ academic success/failure evaluation and the teacher/tutor approximation to the students’ day-by-day academic activities. Although important, the activities involved in these processes do not take place in many higher education institutions, due to the lack of an appropriate support. To sustain these complex processes and activities, a conceptual framework and a technological infrastructure was proposed and integrated in a Student Relationship Management (SRM) System. The SRM System supports the SRM concept and practice and it has been implemented using concepts and technologies associated with the Business Intelligence systems. To validate the SRM System, several application cases were implemented in real contexts. They demonstrated the system relevance in the process of acquisition of knowledge about the students and their academic behaviours. The system supports the decision making process in the teaching/learning scope and facilitates the automatic interaction with the students. The impact of the several undertaken actions are presented and analysed in this paper.